Elementary School Students’ Learning Motivation in Gemiring Lor Village during Online Learning - Nur Emilia Andriyani; Deka Setiawan; Erik Aditia Ismaya (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
This study aims to determine elementary school students’ learning motivation in Gemiring Lor Village during online learning. This study used a qualitative descriptive approach. Informants who were the primary data sources were elementary school students and elementary school teachers in Gemiring Lor Village, Nalumsari District, Jepara Regency. Data were obtained through the process of observation, interviews, documentation, and recording. The validity test employed source triangulation techniques, and data analysis techniques were in the form of data reduction, data presentation, and data conclusion or verification. This study’s findings showed a difference in motivation between one and another student. The students’ motivation level was influenced by environmental factors, such as parents, family, and playmates. Besides, the Gemiring Lor Village teachers had a strategic role in motivating students during the online learning process. This study suggests a particular strategy from the school, teachers, parents, and the student environment to stabilize and increase their motivation.